2011
DOI: 10.1242/jeb.050955
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal processing of translational optic flow in the visual system of the shore crabCarcinus maenas

Abstract: SUMMARYThis paper describes a search for neurones sensitive to optic flow in the visual system of the shore crab Carcinus maenas using a procedure developed from that of Krapp and Hengstenberg. This involved determining local motion sensitivity and its directional selectivity at many points within the neurone's receptive field and plotting the results on a map. Our results showed that local preferred directions of motion are independent of velocity, stimulus shape and type of motion (circular or linear). Globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 96 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…The main function of the lobula is the neural coding of spatial and motion information (via the giant tangential neurones). This is also the case in the lobula of superposition eyes (Horseman et al , 2011). From the lobula, fibres project to the dorsal neuropil of the lateral and medial protocerebrum, from which descending neurones proceed to the neuropils of the neck, leg and flight motor systems.…”
Section: The Optic Lobes and Brainmentioning
confidence: 76%
“…The main function of the lobula is the neural coding of spatial and motion information (via the giant tangential neurones). This is also the case in the lobula of superposition eyes (Horseman et al , 2011). From the lobula, fibres project to the dorsal neuropil of the lateral and medial protocerebrum, from which descending neurones proceed to the neuropils of the neck, leg and flight motor systems.…”
Section: The Optic Lobes and Brainmentioning
confidence: 76%
“…Strausfeld [32] proposed that since the lobula satellite in malacostracans is not LP, optic flow processing should take place in the lobula. While there is a report of neurons possibly involved with translational optic flow in the lobula of crabs [65], no neurons specifically sensitive to rotational optic flow have been found in the lobula so far. Neurons recorded in the lobula of crabs have characteristics compatible with figure detectors, responding more to objects than to panoramic flow-field stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the finding that other malacostracans and the basal hyperiid Cystisoma are equipped with both lobula and lobula plate, and the second optic chiasma (figure 3), the most parsimonious explanation would be a loss of the lobula in H. galba, a loss of the lobula and the ventral lobula plate in P. sedentaria and a loss of both the lobula and the lobula plate in L. sayana (figures 3 and 4). In addition, given that neurons in the lobula are used for computing object features [17], object motion [18][19][20][21][22] and certain flow field information [23], the complete absence of the lobula in H. galba, P. sedentaria and L. sayana are significant secondary reductions of the optic lobes (figures 3 and 4). Likewise, the loss of ventral or entire lobula plate in P. sedentaria and L. sayana, respectively, are additional significant secondary reductions of the optic lobes (figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…The functions of malacostracan optic neuropils have been studied with electrophysiology and optical recording in the brachyuran crabs Neohelice granulata and Carcinus maenas. It was shown that neurons in the lobula are essential for computing object features [17], object motion [18][19][20][21][22] and encoding certain flow field information [23], while those in the lobula plate are implicated in computing wide-field motion and processing optic flow information that mediates optomotor responses [12,13]. Although the experimental evidence came only from a few model species, those functional attributes are generally assumed to apply across malacostracans based on the overwhelming structural conservation and anatomical similarity of those constituent neurons in the optic lobes [12,24].…”
Section: Introductionmentioning
confidence: 99%